2003
DOI: 10.1139/y03-058
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-independent effects of aspirin on cell cycle and putrescine synthesis in human colon carcinoma cells

Abstract: Aspirin consumption has been reported to be able to reduce colorectal cancer risk in humans and in animal models of colon carcinogenesis. Although the mechanism involved in such an effect is not yet clear, both prostaglandin-dependent and -independent effects have been proposed. Using HT-29 Glc(-/+)cells, which originate from a human colon adenocarcinoma, we demonstrated in this study a dose-dependent effect of millimolar concentration of aspirin on cell growth that was concomitant with a rapid accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Previous data demonstrating induction of SAT with aspirin [36] and our data demonstrating increased diamine exporter function with ibuprofen, suggest that augmentation of the diamine exporter -SAT membrane complex may be a mechanism of action that contributes to the cancer chemoprevention provided by aspirin and NSAIDs. Our data demonstrating that the actions of ibuprofen on cellular diamines are not stereospecific are consistent with previous publications demonstrating that the anti-cancer actions of aspirin [12] and NSAIDs [37] are independent of COX inhibition. These observations also suggest that safer analogs devoid of COX inhibition might be optimal drug candidates for cancer chemoprevention.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous data demonstrating induction of SAT with aspirin [36] and our data demonstrating increased diamine exporter function with ibuprofen, suggest that augmentation of the diamine exporter -SAT membrane complex may be a mechanism of action that contributes to the cancer chemoprevention provided by aspirin and NSAIDs. Our data demonstrating that the actions of ibuprofen on cellular diamines are not stereospecific are consistent with previous publications demonstrating that the anti-cancer actions of aspirin [12] and NSAIDs [37] are independent of COX inhibition. These observations also suggest that safer analogs devoid of COX inhibition might be optimal drug candidates for cancer chemoprevention.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the diamine cadaverine, which is generated by ODC metabolism of lysine (Figure 6), is exported via the diamine exporter [17,18,35]. Previous studies of the anti-cancer actions of aspirin have demonstrated that aspirin decreases polyamine synthesis at the level of ODC [12] and increases polyamine metabolism via induction of spermine/spermidine N-acetyltransferase [SAT; [36]]. With our studies of ibuprofen, we did not detect any drug effects on polyamine synthesis; however, we did measure increased cellular efflux of putrescine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these mechanisms is COX-independent [14, 15]. It is well known that activation of p53 expression is involved [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent data suggest that many selective COX-2 inhibitors have multiple chemopreventive mechanisms including induction of apoptosis, which might be important in inhibiting the initiation of cancer, in a COX-2 independent pathway [35,36]. Eklou-Kalonji et al [37] also reported prostaglandin-independent effects of aspirin on cell growth and cell cycle in colon cancer cells. Thirdly, there are no available data demonstrating that curcumin inhibits COX-2 or PGE2 under normal conditions in contrast to an apparent inhibitory effect on highly enhanced COX-2 expression and PGE2 production observed in colon tumors or induced inflammation [38 Á40].…”
Section: Discussionmentioning
confidence: 99%